New approach in models for managing the vessel’s unloading process - Luidmyla, L. Nikolaieva; Taras, Y. Omelchenko; Oleksandr, V. Haichenia (Journal of shipping and trade, 2025)
New way of formalizing hybrid systems in models for managing the vessel unloading process is caused by the significant increase in container transportation around the world over the past decade. The growth of container traffic is the main reason for the constant modernization of port container terminals and improvement of cargo unloading technology is most promising when using those methods, that allow obtaining maximum results in terms of cargo processing speed. This problem is the subject of an article in which analytical review of container handling technologies existing in world ports is carried out, their key performance indicators are formulated and it is shown how the use of a centralized hybrid control system based on the dynamics of discrete events can lead to increased profitability of the port. Developed concept of a hybrid control system makes possible to consider such features of the vessels unload process that have not been considered until now.